Developing Infographic Media on Information and Learning Society in the Three Southern Border Provinces of Thailand - CamKaew, Chutima; Saepun, Warakorn (Journal of Information and Learning [JIL], 2024)
The objectives of this research are 1) to develop the infographic media on information and learning society in the three southern border provinces to meet standards of efficiency, 2) to study the learning effectiveness through infographic media on information and learning society in the three southern border provinces, and 3) to study student satisfaction in using infographic media on information and learning society in the three southern border provinces. This research is an experimental study. The sample group used in this research consisted of undergraduate students majoring in the Bachelor of Arts Programme in Information Science at Yala Rajabhat University who were enrolled in the Information and Learning Society course in the first semester of the academic year 2021, totaling 43 individuals. The research tools included infographic media on information and learning society in the three southern border provinces, a media quality assessment form, an academic achievement test, and a student satisfaction assessment form. Statistical values used in the research include mean, standard deviation, and dependent sample t-test statistics. The research findings revealed that infographic media on information and learning society in the three southern border provinces was of very high quality, with an effectiveness level equal to 82.17/81.71; learners showed a statistically significant increase in learning outcomes compared to their pre-learning scores at a significant level of 0.05; and learners expressed a high level of satisfaction with the use of infographic media on information and learning society in the three southern border provinces. The research results indicate that the development of infographic media can effectively support learning. This is because such media can present complex information in an easily understandable format, promoting the development of students' abilities and skills in understanding information and learning resources in the three southern border provinces efficiently.